2010
DOI: 10.1038/ki.2010.129
|View full text |Cite
|
Sign up to set email alerts
|

Daily oral sodium bicarbonate preserves glomerular filtration rate by slowing its decline in early hypertensive nephropathy

Abstract: In most patients with hypertensive nephropathy and low glomerular filtration rate (GFR), the kidney function progressively declines despite the adequate control of the hypertension with angiotensin-converting enzyme inhibition. Previously we found that 2 years of oral sodium citrate slowed GFR decline in patients whose estimated GFR (eGFR) was very low (mean 33 ml/min). This treatment also slowed GFR decline in an animal model of surgically reduced nephron mass. Here, we tested if daily oral sodium bicarbonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
304
3
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(333 citation statements)
references
References 34 publications
14
304
3
12
Order By: Relevance
“…44 -47 More recently, daily bicarbonate supplementation was reported to halt the progression of proteinuric human CKD without metabolic acidosis. 48 The underlying mechanism of these therapeutic effects could be explained by our present observation that luminal alkalinization suppresses intracellular ROS level in tubular cells. To firmly establish the therapeutic potential of luminal alkalinization, it would be necessary to examine whether other types of proteinuric tubular injury (e.g., diabetic nephropathy and chronic glomerulonephritis) are also attenuated by NaHCO 3 feeding.…”
Section: Effect Of Luminal Alkalinization On Protein-overload Nephropmentioning
confidence: 88%
“…44 -47 More recently, daily bicarbonate supplementation was reported to halt the progression of proteinuric human CKD without metabolic acidosis. 48 The underlying mechanism of these therapeutic effects could be explained by our present observation that luminal alkalinization suppresses intracellular ROS level in tubular cells. To firmly establish the therapeutic potential of luminal alkalinization, it would be necessary to examine whether other types of proteinuric tubular injury (e.g., diabetic nephropathy and chronic glomerulonephritis) are also attenuated by NaHCO 3 feeding.…”
Section: Effect Of Luminal Alkalinization On Protein-overload Nephropmentioning
confidence: 88%
“…it/remission/) and applied to all CKD patients with heavy proteinuria despite therapy. 75 This multimodal intervention strategy included lifestyle modifications such as sodium 93 and protein 30 intake restriction, smoking cessation, body weight loss, 94 optimal BP (target systolic/diastolic ,130/80 mmHg) and metabolic control (target hemoglobin A1C ,7.5%) in patients with diabetes, correction of metabolic acidosis 95 and hyperphosphatemia, 96 use of statins, 76,97,98 and dual RAS blockade with maximum tolerated doses of ACE inhibitors and ARBs, probably the mainstay of proteinuria management in this setting. 99 In a matched-cohort study, we compared the outcome of 56 CKD patients receiving the Remission Clinic approach because of persistent 24-hour proteinuria .3 g despite standard antihypertensive doses of an ACE inhibitor with that of 56 matched historical reference patients who had received ACE inhibitor therapy titrated to target BP.…”
Section: The Remission Clinic Examplementioning
confidence: 99%
“…21 The effects of sodium bicarbonate, sodium chloride, or placebo on the rate of eGFR decline in 120 subjects with macroalbuminuric hypertensive nephropathy demonstrated that after 5 years the rate of eGFR decline was slower in the bicarbonate group. 22 On the basis of this evidence, it is reasonable to maintain serum bicarbonate concentration 422 mmol/l in CKD patients. 2 …”
Section: Bicarbonate Supplementationmentioning
confidence: 99%